2021
DOI: 10.3390/diagnostics11101812
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Mechanical Ventilation and Mortality in COVID-19 Using Radiomics and Deep Learning on Chest Radiographs: A Multi-Institutional Study

Abstract: In this study, we aimed to predict mechanical ventilation requirement and mortality using computational modeling of chest radiographs (CXRs) for coronavirus disease 2019 (COVID-19) patients. This two-center, retrospective study analyzed 530 deidentified CXRs from 515 COVID-19 patients treated at Stony Brook University Hospital and Newark Beth Israel Medical Center between March and August 2020. Linear discriminant analysis (LDA), quadratic discriminant analysis (QDA), and random forest (RF) machine learning cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 44 publications
(139 reference statements)
0
22
0
Order By: Relevance
“…Similar to the proposed study, Aljouie et al [17] and Bae et al [18], proposed a model for two tasks, i.e., mortality and ventilator support prediction for COVID-19-hospitalized patients. In the first study, the author utilized different categories of data and found that comorbidity alone can help in predicting the mortality of COVID-19 patients.…”
Section: Ai-based Studies To Predict Early Mortality In Covid-19 Pati...mentioning
confidence: 81%
See 4 more Smart Citations
“…Similar to the proposed study, Aljouie et al [17] and Bae et al [18], proposed a model for two tasks, i.e., mortality and ventilator support prediction for COVID-19-hospitalized patients. In the first study, the author utilized different categories of data and found that comorbidity alone can help in predicting the mortality of COVID-19 patients.…”
Section: Ai-based Studies To Predict Early Mortality In Covid-19 Pati...mentioning
confidence: 81%
“…Similarly, ref. [15][16][17][18]23] found age as one of the key features for predicting intubation in COVID-19 patients. However, Bae et al [18] used radiomics features and two demographic features (age and gender) to predict mortality and ventilator support.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations